Chicken soup for the soul : thanks mom : 101 stories of gratitude, love, and good times - Canfield, Jack, 1944-; Hansen, Mark Victor; Walker, Wendy, 1967-; Lunden, Joan (Chicken Soup for the Soul, 2009)
A collection of 101 stories from children of all ages relating anecdotes about their mothers and why they are thankful to their mothers.